2013
DOI: 10.5811/westjem.2013.1.12665
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Prehospital Records are Often Unavailable for Emergency Department Medical Decision Making

Abstract: Introduction:To determine emergency physician (EP) opinions of prehospital patient care reports (PCRs) and whether such reports are available at the time of emergency department (ED) medical decision-making.Methods:Prospective, cross-sectional, electronic web-based survey of EPs regarding preferences and availability of prehospital PCRs at the time of ED medical decision-making.Results:We sent the survey to 1,932 EPs via 4 American College of Emergency Physicians (ACEP) email lists. As a result, 228 (11.8%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
3
12
0
1
Order By: Relevance
“…These benefits correlate with the findings of others that use of EMR provides benefits in the emergency medical services setting for paramedics, ambulance services, and academia (Bledsoe et al, 2013;Katzer et al, 2012;Newgard et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These benefits correlate with the findings of others that use of EMR provides benefits in the emergency medical services setting for paramedics, ambulance services, and academia (Bledsoe et al, 2013;Katzer et al, 2012;Newgard et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Eighty-nine percent of hospital emergency department physicians surveyed in the United States reported that the paramedics' written medical chart was important or very important to their emergency department medical practice. Those same physicians overwhelmingly preferred an electronic record to a hand written chart, 52% vs. 17% (Bledsoe et al, 2013).…”
Section: Changing Systems and Processesmentioning
confidence: 99%
“…A large survey of the American College of Emergency Physicians (ACEP) physicians demonstrated that 89% of physicians felt that prehospital records were either "very important" or "important" to their ED practice, but were usually unavailable at the time of medical decision-making. 12 In keeping with this finding, 81.1% of patients in our study did not have an ACR available to the treating physician at the time of initial assessment, and 69.5% did not have an ACR available at any point during ED care. This finding is contrary to the NAEMSP position that the complete EMS patient care report must be made available to the receiving facility within a clinically relevant period of time.…”
Section: Discussionsupporting
confidence: 51%
“…While previous research has demonstrated the general value of the ACR, and the fact that physicians perceive the ACR as an important tool, we were able to show that physicians believed that the ACR changed management in 28.8% of specific patient encounters. 11,12 In our study, physicians did not receive an ACR or verbal handover from a nurse or paramedic in half of patients (50.5%), highlighting the possible loss of valuable prehospital information, which could result in improper or inadequate workups, treatments, and disposition decisions. Although physicians regard prehospital information from paramedics as relevant and important to patient care, handover is often incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation